Construction of tunnel form system / Muhammad Luqman Darduri - Darduri, Muhammad Luqman (2017)
With technological advancements and innovative architectural design, tunnel form is being adopted for all kinds of projects from luxury apartments and villas through to 5 star hotels and commercial buildings, Tunnel form is also being used in hybrid buildings in order to speed up the construction process. Already able to do spans of 7.5m by 15m +/- depth, we have now developed a system combined with a lightweight slab to allow a single space of 9 metres width and 15 metres+ depth to complete both concrete walls and slab in just 1 day...a space of 120m2+ ! Yes an area bigger than the average home can now be achieved in one day with Tunnel Form Construction. Is completely steel & made specifically to the project design that can be readily modified for subsequent projects. This is paramount as a quality made tunnel formwork is an investment in solid steel designed to last upto 1000 reuses/floors of building and thereforewill last for the completion of many projects with only small modular adaptations needed from project to project. Invented over 50 years ago and initially used to form repetitive cellular structures. Tunnel form is widely recognised as a modern construction method that enables the construction of horizontal and vertical elements simultaneously. Used worldwide by astute developers to quickly construct low cost, high quality and earthquake safe to construct cellular buildings such as hotels, low and high-rise housing, hostels, student accommodation, condominiums, assisted living residences, prison and barracks accommodation and luxury villa complexes from the USA to the UAE